ISLAMIC POLITICAL HISTORY REFORM MOVEMENT IN PAKISTAN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2025)
This study aims to trace the history of Islam in Pakistan and to examine the reform ideas of Sayyid Ahmad Khan, Muhammad Iqbal and Muhammad Ali Jinnah. Political development in Pakistan was quite high due to frequent upheavals, crises and military coups in the first few years of its formation and the years that followed. The inability of the leaders to manage the government resulted in riots in various regions and ever-changing political movements. Under Ali Butto, the system of government was changed from Islamic to secular, which led to disappointment with Butto's leadership and ended in a military coup. In the next development during the Zia Ul-Haq era, there was development in all aspects of life that could improve governance and change back to an Islamic ideological system. Data collection in this research uses the documentation method. The main data sources were obtained through literature studies and other studies that have relevance to the research topic. Then the data obtained were analyzed through three stages, namely data reduction, data presentation, and conclusions.